Citizenship and the passive revolution: interpreting the first amendment - Menon, Nivedita (2004)
Modernity as has been argued, is a set of processes that can follow different sequences in different societies and at different historical conjunctures; in India unlike in the west, the two processes of modernity and democracy emerged almost simultaneously. This paper explores the dilemmas created by the 'different sequentiality' by focusing on one revealing moment - the 1951 Act that first amended by the Constitution, interpreted here as a landmark in the story of modernity in India. While the amendment was seen to limit individual rights it reflected primarily the imperatives of the modernising project envisaged by India's anti-imperialist elite that included the creation of a bourgeois democracy, the capitalist transformation of the economy and the establishment of social justice. - Reproduced.
Keywords: India - Constitution; Constitutions